Synthesis of NiFe2O4 Photocatalyst to Apply for Treatment of Residual Tetracycline in Aqueous Environment with Addition of H2O2 - Duc, Dang Minh; Hang, Cat Minh; Van, Dinh Tuong; Khoa, Nguyen Viet; Linh, Tran Thuy; Hanh, Nguyen Thi; Dong, Pham Thanh (VNU Journal of Science: Natural Sciences and Technology, 2024)
In the study, NiFe 2 O 4 was successfully synthesized by hydrothermal method for treatment of residual tetracycline (TC) in aqueous environment. The study also investigated effects of H 2 O 2 as electron an acceptor to enhance TC photocatalytic degradation of the synthesized NiFe 2 O 4 . The properties of synthesized materials were determined by scanning electron microscopy (SEM), X-ray diffraction (XRD), UV-Vis absoprtion spectroscopy (UV-VIS) and vibrating sample magnetometer (VSM) systems. The obtained results indicated that the synthesized NiFe 2 O 4 were nano-particles with average size of approximately 50 nm. The synthesized NiFe 2 O 4 also exhibited high visible light absorption and magnetic ability. The TC removal results indicated that the NiFe 2 O 4 adsorbed certain amount of tetracycline under dark condition. Under visible light, the NiFe 2 O 4 further degraded significant tetracycline amount. Finally, the study investigated that H 2 O 2 effectively acted as electron acceptor for hydroxyl radical production to degrade tetracycline.